Association Between Metabolic Syndrome and Cardiac Autonomic Nervous Function and Cardiorespiratory Fitness in Older Adults: A Retrospective Observational Study with Propensity Score Overlap Weighting - Cui N; Li Q; Cheng J; Xing T; Shi P; Wang Y; Luo M; Dun Y; Liu S (Clinical Interventions in Aging)
Ni Cui,1,* Qiuxia Li,1,* Jing Cheng,2,* Tianhua Xing,1 Peiyao Shi,3 Yingmei Wang,2 Min Luo,2 Yaoshan Dun,1,4 Suixin Liu1,4 1Division of Cardiac Rehabilitation, Department of Physical Medicine & Rehabilitation, Xiangya Hospital of Central South University, Changsha, Hunan, 410008, People’s Republic of China; 2Department of Cardiovascular medicine, Shenzhen District Yantian People’s Hospital, Shenzhen, Guangdong, 518081, People’s Republic of China; 3Department of Experimental Diagnosis, Shenzhen District Yantian People’s Hospital, Shenzhen, Guangdong, 518081, People’s Republic of China; 4National Clinical Research Center for Geriatric Disorders, Xiangya Hospital of Central South University, Changsha, Hunan, 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Suixin Liu; Yaoshan Dun, Division of Cardiac Rehabilitation, Department of Physical Medicine & Rehabilitation, Xiangya Hospital of Central South University, Changsha, Hunan, 410008, People’s Republic of China, Email liusuixin@csu.edu.cn; dunyaoshan@csu.edu.cnBackground: Delayed heart rate recovery (HRR) after exercise, an indicator of cardiac autonomic nervous function (CANF), has been found to be associated with metabolic syndrome (MetS) in general populations. However, this relationship has not been extensively studied in older adults. The present study aimed to investigate the association between MetS and HRRs at 1, 2, 3 and 6 minutes after exercise and cardiorespiratory fitness (CRF) in Chinese dwelling older adults.Methods: This retrospective, observational study consecutively enrolled participants aged 60 years or older who underwent physical examinations in Shenzhen District Yantian People’s Hospital from September 2019 to July 2021. The participants were categorized into MetS and non-MetS groups according to the International Diabetes Federation criteria. Logistic regression analysis was applied to assess the association between MetS and CANF and CRF. Propensity score overlap weighting was used to adjust the covariates.Results: A total of 987 eligible participants were included (mean age±SD, 66± 4 years; male, 47.1%), of whom, 506 were diagnosed with MetS. MetS group showed significantly lower peak heart rate, HRR1-3, HRR6, peak metabolic equivalents, and peak oxygen consumption compared to the non-MetS group. Furthermore, peak systolic and diastolic blood pressures in the MetS group were significantly higher. Logistic regression analysis showed that MetS was significantly associated with HRR2, HRR3 (odds ratio [95% CI], 0.997 [0.995,0.999], both; P=0.009 and 0.005, respectively) and HRR6 (0.996 [0.994,0.998], P< 0.001). The association between MetS and CRF was significant (0.98 [0.97,0.98], P< 0.001).Conclusion: Elderly Chinese with MetS tend to exhibit reduced CANF and lower CRF. It is recommended that they boost physical activity and closely monitor heart rate and blood pressure during exercise to mitigate exercise-related risks.Keywords: aging population health, heart rate recovery, systolic blood pressure recovery, geriatric cardiology, autonomic regulation, fitness evaluation